Utilization of Moringa Leaf Extract in Processed Pudding Products as an Effort to Prevent Stunting in Debong Lor Village Tegal City - Nugroho, Pramudya Panji; Mahendra, Okka Issa; Shidqi, Adnan Maulana; Ramadhani, Lusiana; Ramadhani, Safira; Imroatus S., Yusnia; Wati, Rhahma; Afifah, Irun; Oktriana, Oktriana; Arina, Faula; Khofifah, Novia Eka; Putri, Imram Radne Rimba; M. F., Fristi Nadila (AMK : Abdi Masyarakat UIKA, 2024)
Stunting is a failure in the development and growth of children due to malnutrition. Nutrition is one of the determining factors for the growth and development of a child. Moringa plants are one of the plants that have high nutritional content, and their leaves can be used as one of the basic ingredients for food or beverage processing. The activity of providing supplementary food (PMT) in the form of moringa leaf pudding to prevent stunting was carried out in various posyandu in the Debong Lor Village, West Tegal District, with the participation of mothers who have toddlers/cludas and pregnant women. The method used in this service is the counseling method by providing supplementary food (PMT) and introducing one of the processed moringa leaves that can be useful to prevent stunting, namely moringa leaf pudding. The result of this activity is that young women have an interest in processing moringa leaves to prevent stunting.